The natural history of intracranial cavernous malformations - Bradley A. Gross; Ning Lin; Rose Du; Arthur L. Day (2011)
Literature reports on the natural history of cerebral cavernous malformations (CMs) are numerous, with considerable variability in lesion epidemiology, hemorrhage rates, and risk factors for hemorrhage. In this review, the authors performed a meta-analysis of 11 natural history studies. The overall male-to-female ratio was 1:1, and the mean age at presentation was 30.6 years. Overall, 37% of patients presented with seizures, 36% with hemorrhage, 23% with headaches, 22% with focal neurological deficits, and 10% were asymptomatic. Some patients had more than one symptom. Seizure presentation was most prevalent among supratentorial CMs, while focal neurological deficits were common in patients with infratentorial CMs. By location, CMs were in the cerebral hemispheres (66%), brainstem (18%), basal ganglia or thalamus (8%), cerebellum (6%), and other (2.5% [combined supra- and infratentorial, callosal or insular]). Overall, 19% of patients harbored multiple intracranial CMs, and 9% had radiographically apparent associated developmental venous anomalies. An overall annual hemorrhage rate of 2.4% per patient-year (range 1.6%–3.1%) was identified across 3 studies. Prior hemorrhage and female sex were risk factors for bleeding, while CM size and multiplicity did not affect hemorrhage rates. Although not impacting the hemorrhage rate itself, deep location was a risk factor for increased clinical aggressiveness.